2006
DOI: 10.1366/000370206778062101
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Ring-down Spectroscopy for Detection in Liquid Chromatography: Extension to Tunable Sources and Ultraviolet Wavelengths

Abstract: In earlier studies, it was demonstrated that the sensitivity of absorbance detection in liquid chromatography (LC) can be improved significantly by using cavity ring-down spectroscopy (CRDS). Thus far, CRDS experiments have been performed using visible laser light at fixed standard wavelengths, such as 532 nm. However, since by far most compounds of analytical interest absorb in the ultraviolet (UV), it is of utmost importance to develop UV-CRDS. In this study, as a first step towards the deep-UV region, LC se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…A comparison between this study and previous liquid-phase cavity studies as a function of technique, the mirror reflectivity, base path length, the wavelength of measurement, the lowest value of a min , the minimum LOD for an analyte, and the molar extinction coefficient e for that analyte. 1.06 3 10 5 Xu et al 19 CRDS 0.9997 1 607 1 3 10 À5 ÁÁÁ ÁÁÁ Snyder et al 20 CRDS 0.9993 0.03 470 2.5 3 10 À4 9.2 3 10 À8 9 3 10 3 Hallock et al 22 CRDS 0.9998 21 620-670 1 3 10 À6 ;1 3 10 À11 1 3 10 5 Hallock et al 23 CRDS 0.9998 23 655 3.3 3 10 À7 ÁÁÁ ÁÁÁ Bechtel et al 24 CRDS ÁÁÁ 0.03 488 2.6 3 10 À6 1 3 10 À7 ÁÁÁ Bahnev et al 25 CRDS 0.9998 0.2 532 1.6 3 10 À4 3.7 3 10 À9 5.45 3 10 4 van der Sneppen et al 26 CRDS 0.99 996 0.2 532 1.0 3 10 À5 1.5 3 10 À8 1.4 3 10 4 van der Sneppen et al 27 CRDS 0.99 993 0.2 457 1.0 3 10 À5 1.2 3 10 À8 3.6 3 10 4 van der Sneppen et al 27 CRDS 0.9995 0.2 355 5.0 3 10 À5 7.5 3 10 À8 1.02 3 10 4 Fiedler et al 28 BBCEAS 0.99 1 607 2 3 10 À5 ÁÁÁ ÁÁÁ Fiedler et al 28 analyte in question. These are compared with corresponding data, where available, from the small number of previous liquid-phase cavity studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison between this study and previous liquid-phase cavity studies as a function of technique, the mirror reflectivity, base path length, the wavelength of measurement, the lowest value of a min , the minimum LOD for an analyte, and the molar extinction coefficient e for that analyte. 1.06 3 10 5 Xu et al 19 CRDS 0.9997 1 607 1 3 10 À5 ÁÁÁ ÁÁÁ Snyder et al 20 CRDS 0.9993 0.03 470 2.5 3 10 À4 9.2 3 10 À8 9 3 10 3 Hallock et al 22 CRDS 0.9998 21 620-670 1 3 10 À6 ;1 3 10 À11 1 3 10 5 Hallock et al 23 CRDS 0.9998 23 655 3.3 3 10 À7 ÁÁÁ ÁÁÁ Bechtel et al 24 CRDS ÁÁÁ 0.03 488 2.6 3 10 À6 1 3 10 À7 ÁÁÁ Bahnev et al 25 CRDS 0.9998 0.2 532 1.6 3 10 À4 3.7 3 10 À9 5.45 3 10 4 van der Sneppen et al 26 CRDS 0.99 996 0.2 532 1.0 3 10 À5 1.5 3 10 À8 1.4 3 10 4 van der Sneppen et al 27 CRDS 0.99 993 0.2 457 1.0 3 10 À5 1.2 3 10 À8 3.6 3 10 4 van der Sneppen et al 27 CRDS 0.9995 0.2 355 5.0 3 10 À5 7.5 3 10 À8 1.02 3 10 4 Fiedler et al 28 BBCEAS 0.99 1 607 2 3 10 À5 ÁÁÁ ÁÁÁ Fiedler et al 28 analyte in question. These are compared with corresponding data, where available, from the small number of previous liquid-phase cavity studies.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 A few studies have applied liquidphase CRDS to high-performance liquid chromatography (HPLC) systems. [24][25][26][27] Currently, only two studies using CEAS for liquid-phase measurements have been reported. Fielder et al 28 made cuvette based measurements at normal angles of incidence using BBCEAS in a modified conventional double beam ultraviolet (UV)-visible spectrometer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of the absorption coefficient of an analyte does, however, require the reflectivity of the mirrors to be known, or more typically a separate calibration to be performed. The experimental difficulty in using CRDS increases when experimental schemes employ short cavity lengths such as those used by van der Sneppen et al 12,13 as these lead to shorter ring down times, which are worsened by the inherent high losses present in liquid-phase studies. These limit the range of analyte concentrations which can be studied before the ring down time becomes too short to measure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, liquid-phase CRDS has received much attention, and its potential in analytical chemistry has been demonstrated. It has been shown that compared to conventional absorbance detection, the baseline noise and limits of detection (LODs) in liquid chromatography (LC) can be significantly improved (1)(2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%